Is adenomyosis, a frequent association of abnormal uterine bleeding? : a retrospective study on hysterectomy samples in the rural area of Melmaruvathur - S., Sumathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Abnormal uterine bleeding is one of the common gynecological problem and the causes varies among different age groups. The objective of the study was to find the prevalence of adenomyosis among hysterectomy samples of rural patients and associated pathological lesions as a cause for abnormal uterine bleeding. Methods: A retrospective cross sectional study was carried out in pathology department of Melmaruvathur Adhiparasakthi institute of medical sciences from Jan 2014 to Dec 2015.A total of 82 hysterectomy samples operated for abnormal uterine bleeding were analyzed both grossly and microscopically. Results: The common pathology noted was adenomyosis 56% followed by leiomyoma 35%. The mean age of patients commonly affected was 45.86 years with a confidence interval of 95% (43-46years). Conclusions: Adenomyosis is a frequent association of abnormal uterine bleeding and it commonly affects perimenopausal age group patients of 43-46years. Benign pathology is a frequent finding and malignant lesion is very rare.